The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1099/vir.0.80365-0
|View full text |Cite
|
Sign up to set email alerts
|

Important B-cell epitopes for neutralization of human immunodeficiency virus type 1 Tat in serum samples of humans and different animal species immunized with Tat protein or peptides

Abstract: The Tat regulatory protein of human immunodeficiency virus type 1 (HIV-1) is secreted by infected cells and plays a key role in viral pathogenesis and replication. Tat protein has been proposed as a target antigen for vaccine design since anti-Tat antibodies may interfere with virus spread and disease progression. The aim of this study was to analyse the serum antibody response of mice, rabbits, macaques and humans immunized with recombinant Tat, synthetic Tat, Tat toxoid or Tat peptides and to examine the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Both dsRNA motifs potentiated the anti-Tat antibody responses, which were comparable to those elicited in the presence of CT. Analysis of the fine-specificity of anti-Tat IgG antibodies using synthetic peptides revealed strong reactivity with peptides 1-20 and 44-61, which represent important epitopes [10,[19][20][21][22][31][32][33][34][35]. However, only sera of mice immunized with sTat and pI:pC motif inhibited Tat-driven transactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both dsRNA motifs potentiated the anti-Tat antibody responses, which were comparable to those elicited in the presence of CT. Analysis of the fine-specificity of anti-Tat IgG antibodies using synthetic peptides revealed strong reactivity with peptides 1-20 and 44-61, which represent important epitopes [10,[19][20][21][22][31][32][33][34][35]. However, only sera of mice immunized with sTat and pI:pC motif inhibited Tat-driven transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of serum antibodies was determined using ELISA plates coated with peptides 1-20 and 44-61, which have been reported to represent critical neutralizing B cell epitopes of Tat protein [19][20][21][22] and have limited antigenic polymorphism among HIV-1 strains [23]. Although all tested sera reacted with both peptides (Fig.…”
Section: Dsrna Motifs Inhibit Tat-driven Transactivationmentioning
confidence: 99%
“…In addition, evidence exists that natural IgM antibodies reacting with Tat may provide an early initial defense against the pathological effects of Tat after HIV infection and influence the course of AIDS progression [131,132]. Similarly, immunization with Tat elicits antibody responses in rodents, monkeys, and humans able to block the activity of extracellular Tat on cellular entry, gene expression, and replication [4,84,[133][134][135][136][137][138][139][140][141][142]. Moreover, strong anti-Tat antibody responses correlated with an efficient reduction in plasma viremia and long-term protection in Tat protein-vaccinated monkeys challenged intrarectally with an heterologous SHIV virus [143].…”
Section: The Choice Of Tat As Vaccine Relevant Antigenmentioning
confidence: 99%
“…It has been recently shown that antibodies directed against the N-terminus region of Tat, which is the most immunogenic in terms of humoral responses, 32,33 protect monkeys from infection acquisition, 15 suggesting that the Tat 1-20 peptide constitutes an interesting candidate for a preventive vaccine. To assess how different routes of administration may affect humoral immunogenicity of peptide vaccines, mice were vaccinated 3 times (at days 1, 14 and 28), by ID or OM route, with Tat 1-20 peptide (EPVDPRLEPWKHPGSQPKT, synthesized by solid phase method and purified by HPLC to >98% purity by UF Peptides, University of Ferrara, Italy), encompassing an immunodominant Tat epitope, 32,33 at the dose of 7mg.…”
mentioning
confidence: 99%
“…To assess how different routes of administration may affect humoral immunogenicity of peptide vaccines, mice were vaccinated 3 times (at days 1, 14 and 28), by ID or OM route, with Tat 1-20 peptide (EPVDPRLEPWKHPGSQPKT, synthesized by solid phase method and purified by HPLC to >98% purity by UF Peptides, University of Ferrara, Italy), encompassing an immunodominant Tat epitope, 32,33 at the dose of 7mg. This dose contains the same number of molecules of 30mg of Tat protein.…”
mentioning
confidence: 99%